Tren Childfree dan Unmarried di kalangan Masyarakat Jepang - Dhimas Adi Nugroho; Fitri Alfarisy; Afizal Nuradhim Kurniawan; Elin Rahma Sarita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The entry of western cultural influences into Japan brought various kinds of trends, both in the form of technology, science and trends, one of which is the trend of child-free and unmarried, this trend began to be followed by Japanese people, especially in urban areas. child-free and unmarried trends. This research uses descriptive analysis method, describes the current trends in Japanese society, and data obtained from literature studies. The development of this trend has had a major impact on Japan, especially women and on the rate of population growth, the patriarchal culture that has existed for a long time has spurred Japanese women to voice their rights in self-determination. The feminist movement developed and had a great influence on Japanese women. From this trend, it can be concluded that population problems are starting to emerge, including the increasing number of elderly people and the low rate of population growth. In addition, the Japanese government's efforts have emerged so that the rights of Japanese women are fulfilled and population growth increases